Systemic Lupus Erythematosus–associated Diffuse Alveolar Hemorrhage: A Case Report and Review of the Literature. Issue 5 (September 2018) - Morales-Nebreda, Luisa; Alakija, Omolola; Ferguson, Keith T.; Singer, Benjamin D.
Abstract : Systemic lupus erythematosus is associated with numerous pleuropulmonary complications. Although uncommon, diffuse alveolar hemorrhage (DAH) represents a life-threatening cause of acute respiratory failure among patients with lupus. Here, we present a 24-year-old woman with a history of lupus who developed hemoptysis and respiratory failure associated with diffuse radiographic infiltrates and anemia. Bronchoscopy confirmed DAH. She was managed with supportive care, plasmapheresis, and immunosuppressive pharmacotherapy, leading to sustained resolution of her pulmonary hemorrhage and respiratory failure. We review the available literature on the pathophysiology and management of lupus-associated DAH, which centers on supportive care, reversal of coagulopathy, and immunosuppressive measures.